Organic matter deposition along the Kara and Laptev Seas continental margin (eastern Arctic Ocean) during the last deglaciation and Holocene: evidence from organic-geochemical and petrographical data. - Boucsein, Bettina; Knies, Jochen; Stein, Ruediger (PANGAEA, 2002)
Organic petrologic (maceral analysis) and bulk organic-geochemical studies were performed on five sediment cores from the Eurasian continental margin to reconstruct the environmental changes during the last not, vert, similar13 000 yr. The core stratigraphy is based on AMS-14C dating, and correlation by magnetic susceptibility and lithostratigraphic characteristics. Variations in terrigenous, freshwater, and marine organic matter deposition document paleoceanographic and paleoclimatic changes during the transition from the last deglaciation to the Holocene. Glacigenic diamictons deposited in the St. Anna Trough (northern Kara Sea) during the Last Glacial Maximum (LGM) are characterized by reworked terrigenous organic matter. In contrast, the Laptev Sea shelf was not covered by an ice-sheet, but was exposed by the lowered sea level. Increased deposition of marine organic matter (MOM) during deglaciation indicates enhanced surface-water productivity, possibly related to influence of Atlantic waters. The occurrence of freshwater alginite gives evidence for river discharge to the Kara and Laptev Seas after the LGM. At the eastern Laptev Sea slope, the first influence of Atlantic water masses is indicated by an increase in the contents of MOM and dinoflagellate cysts, with Operculodinium centrocarpum prior to not, vert, similar10 000 yr BP. High sedimentation rates in the Kara and the Laptev Seas with the adjacent slope at the beginning of the Holocene are presumably related to increased freshwater and sediment discharge from the Siberian rivers. Evidence for elevated Holocene freshwater discharge to the Laptev Sea has been found between not, vert, similar9.8 and 9 kyr BP, at not, vert, similar5 kyr BP and at not, vert, similar2.5 kyr BP. In the Kara Sea, an increased freshwater signal is obvious at not, vert, similar8.5 kyr BP and at not, vert, similar5 kyr BP. Higher portions of MOM were accumulated in the St. Anna Trough and at the Eurasian continental margin at several intervals during the Holocene. Increased primary productivity during these intervals is explained by seasonally ice-free conditions possibly associated with increased inflow of Atlantic waters.
Organic matter deposition along the Kara and Laptev Seas continental margin (eastern Arctic Ocean) during last deglaciation and Holocene
Keywords: ARK-IX/4; ARK-XI/1; AWI_Paleo; Gravity corer (Kiel type); Gravity corer (Russian type); Kara Sea/St. Anna Trough; Laptev Sea; Paleoenvironmental Reconstructions from Marine Sediments @ AWI; PL-1994; PL94-08; PL94-60; Polarstern; Professor Logachev; PS2476-4; PS27; PS27/062; PS2742-5; PS36; PS36/030; Quaternary Environment of the Eurasian North; QUEEN; RGC; SL